Academic resilience among Malaysian secondary school students: a confirmatory factor analysis - Sulong, Rose Manisah; Ahmad, Nor Aniza; Che Hassan, Norlizah; Zainudin, Zaida Nor; Ismail, Maimunah (Human Resource Management Academic Research Society, 2019)
Academic resilience refers to the ability of students to maintain motivation and achieve success in academics despite the presence of risk factors that put themselves at risk for failing and dropping out (Benard, 1991; Alva, 1991; Gonzalez & Padilla, 1997; Finn & Rock, 1997). Hence, studying and understanding the factors that make these students successful is important in helping them improve their academic performance. The purpose of the study is to validate the measurement model based on Resilience Theory (Benard, 1991). The proposed measurement model comprises three constructs, namely school external protective factors, resilience traits and academic achievement. This study involved a total of 315 secondary school students in the East Coast of Peninsular Malaysia. The findings show that the proposed measurement model fits the survey data. Therefore, through the actual data, the measurement model can be used to confirm the Resilience Theory.